Diagnostic criteria in amyotrophic lateral sclerosis: A multicenter prospective study. (16th August 2016) - Geevasinga, Nimeshan; Menon, Parvathi; Scherman, Daniel B.; Simon, Neil; Yiannikas, Con; Henderson, Robert D.; Kiernan, Matthew C.; Vucic, Steve
Abstract : Objective: To assess the sensitivity and specificity of the Awaji and revised El Escorial diagnostic criteria (rEEC) in amyotrophic lateral sclerosis (ALS). Methods: We conducted a large prospective multicenter study, recruiting 416 patients (253 male, 163 female) between January 1, 2012, and August 31, 2015, to compare the diagnostic accuracy of Awaji and rEEC in accordance with standards of reporting of diagnostic accuracy criteria. Results: The sensitivity of the Awaji criteria (57%, 50.0%–63.3%) was higher when compared to rEEC (45%, 38.7%–51.7%, p < 0.001), translating to a 12% gain in sensitivity. The specificity of the both criteria were identical, 99.5%, indicating the number needed to test in order to diagnose one extra case of ALS was 1.8 (1.5–2) for Awaji criteria and 2.4 (2–2.6) for rEEC. The Awaji criteria exhibited a higher sensitivity across subgroups, including bulbar ( p < 0.001) and limb-onset ( p < 0.001) patients. The inclusion of the possible diagnostic category as a positive finding enhanced sensitivity of the Awaji criteria and rEEC, particularly in early stages of ALS, while maintaining specificity. Conclusion: The present study established a higher sensitivity of Awaji criteria when compared to rEEC, with diagnostic benefits evident in bulbar and limb-onset disease. Inclusion of possible as a positive finding enhanced sensitivity of both criteria, while maintaining specificity, and should be considered in clinical practice and future therapeutic trials. Classification of evidence: This study provides Class IV evidence that the Awaji criteria have a higher sensitivity and the same specificity as the rEEC in identifying patients with ALS.